2013
DOI: 10.1002/phy2.129
|View full text |Cite
|
Sign up to set email alerts
|

Reticular activating system of a central pattern generator: premovement electrical potentials

Abstract: For the first time, here we characterize a bulbar reticular activating system (RAS) of neurons in decerebrate, deafferented and decerebellated cats producing a premovement electrical potential that we named obex slow potential (OSP). The OSP occurs about 0.8 ± 0.4 sec prior to the onset of a fictive-scratching-episode. Here, we describe two classes of bulbar neurons, off-on, which are silent but exhibit a 80 ± 56 Hz firing discharge at the beginning of (and during) the OSP, and on-off interneurons, with a 27 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…The magenta histogram in Figure 3A illustrates the mean latency between the functional DC-PPG signal of the brainstem (red triangle) versus the functional DC-PPG signal of the spinal cord (red triangle) for these two animals in 74 scratching episodes (mean latency = 1.7 ± 0.4 s). As expected, this latency between both DC-PPG signals is similar to the latency between the obex slow potential and the spinal cord DC-shift associated with the scratching episodes (see Tapia et al, 2013). All relevant data is contained within the manuscript.…”
Section: Second Type Of Experiment: Implementation Of the Functional supporting
confidence: 77%
See 1 more Smart Citation
“…The magenta histogram in Figure 3A illustrates the mean latency between the functional DC-PPG signal of the brainstem (red triangle) versus the functional DC-PPG signal of the spinal cord (red triangle) for these two animals in 74 scratching episodes (mean latency = 1.7 ± 0.4 s). As expected, this latency between both DC-PPG signals is similar to the latency between the obex slow potential and the spinal cord DC-shift associated with the scratching episodes (see Tapia et al, 2013). All relevant data is contained within the manuscript.…”
Section: Second Type Of Experiment: Implementation Of the Functional supporting
confidence: 77%
“…With this idea, we performed experiments in seven adult cats (2.3-3.7 kg). Our experimental procedures are similar to those employed in previous reports from our group (Cuellar et al, 2009(Cuellar et al, , 2018Tapia et al, 2013;Meza et al, 2019). The animals were handled with care and introduced in a comfortable anesthesia-induction-box at a temperature of 22-29 • C and 40-70% relative humidity.…”
Section: Animal Preparationmentioning
confidence: 99%
“…In 2013, Tapia et al suggested that arousal state was related to muscular activation which was mediated by the descending reticular activating system. 18 Therefore, to the best of our knowledge, this is the first study to demonstrate injury of the lower portion of the ARAS between the pontine RF and the ILN in patients with mild TBI. Nevertheless, limitations of this study should be considered.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, descending tracts involving the bulbar reticular activating system that were not injured could contribute in the successful rehabilitation. [ 26 ] Second, we examined the main causes of gait inability in this patient (severe physical deconditioning and truncal ataxia) and designed an intensive rehabilitation program to resolve these problems within 2 months. At the start of rehabilitation, the patient could not even sit independently; however, after rehabilitation, the patient was able to walk independently.…”
Section: Discussionmentioning
confidence: 99%